Herpes Virus Prevalence in Patients with Chronic Periodontal Disease and Aggressive Periodontal Disease - Ortiz Pérez DDS, Sergio (2016)
Periodontitis is defined as an inflammatory disease of the supporting tissues of teeth caused by microorganisms or groups of specific microorganisms, which result in progressive destruction of the periodontal ligament and alveolar bone, caused by multiple infectious agents and is interconnected with the humoral and cellular immune responses of the host. This study aimed to determine the prevalence of herpes simplex virus type 1 and 2 and cytomegalovirus in patients with chronic and aggressive periodontits and healthy subjects. Biopsies samples were taken from patients presenting to the clinic of the Universidad Autonoma de Nuevo Leon diagnosed with chronic periodontitis o aggressive periodontitis and control patients. The samples taken were submitted to polymerase chain reaction (PCR) to detect the presence of the virus. The presence of the different kinds of virus was negative in the evaluated subjects.